Reflections on isotimia and citizenship in some Thessalian decrees (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2024)
This paper aims to reflect on the significance of the concession of isotimia, literally “equality of rights”, and its association with the epigraphic formula pathontessi kai drasantessi (abbreviated hereafter as path-/dras-) in Thessalian decrees, and to explore its relationship with other honors granted to foreign benefactors, particularly citizenship. The first part of the essay focuses on identifying and analyzing documents where isotimia appears alongside the path-/dras- formula. The second part extends the investigation to literary and epigraphic documents deemed useful for clarifying the value of isotimia. The conclusion drawn is that isotimia is not entirely synonymous with citizenship, which encompasses it, but rather represents an attribute of it. Isotimia explicitly articulates a prerogative that is inherently implied in naturalization, namely the ability for naturalized citizens to share rights that belong to native citizens. When combined with the path-/dras- formula, isotimia delineates the equality of rights from both an active perspective (holding public office) and a passive one (submitting to the authority of magistrates).
Keywords: Ancient History; Thessaly; Greek Epigraphy; Citizenship; Honorary Decrees